Erroneous intracranial pressure measurements from simultaneous pressure monitoring and ventricular drainage catheters - Birch, A.A.; Eynon, C.A.; Schley, D. (Humana Press Inc, 2006)
The objective of this report is to highlight the potential for false pressure measurements from systems that combine intracranial pressure (ICP) measurement and ventricular drainage. If the ports of the drain become blocked to the extent that they present a high resistance to cerebrospinal fluid flow, then a significant pressure gradient between the inside and outside of the catheter may be established. Thus, any intracatheter transducer will faithfully record a pressure much lower than true ICP. This holds true for catheter-tip transducers when the transducer lies inside the catheter. In the absence of flow, however, pressures will equalize; therefore, accurate measurements may be taken if the drain is temporarily closed. We model this situation and provide simulations of expected measurements in such situations; these compare well to observed clinical readings.
Keywords: Cerebrospinal fluid; Intracranial pressure; Ventricular drainage